2023
DOI: 10.31812/ed.579
|View full text |Cite
|
Sign up to set email alerts
|

On the question of the establishment and development of languages education in Canada (XVII - the beginning of XXI century)

Valeriia V. Ustymenko,
Vita A. Hamaniuk

Abstract: The article is devoted to the study of the theoretical and organizational foundations of language teaching in the Canadian education system in the context of globalization processes and multilingual society. The work presents a retrospective analysis of the formation and development of language teaching in the Canadian education system from the beginning of organized education to the beginning of the 21st century, highlights certain issues of state regulation in the field of language education in Canada. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The state and prospects of future natural sciences teachers training was the subject of our study [19]. Regarding bilingual education, the analysis of literature sources showed that the theoretical foundations of bilingualism in Ukraine are reflected in the works of Baditsa, Kolesnyk and Polkhovska [3], Bodnarchuk [5], Goroshkina [6], Ihnatenko [7], Konoval et al [9], Kotlovskiy et al [10], Shirin [18], Sulik [20], Sytnyakivska and Khlyvnyuk [22], Ustymenko and Hamaniuk [23]. Their researches prove that bilingual education is a purposeful process of involvement in the world culture through native and foreign languages, when a foreign language acts as a means of cognizing the world, acquiring special knowledge, learning cultural, historical and social experience of different countries and peoples.…”
Section: Introductionmentioning
confidence: 99%
“…The state and prospects of future natural sciences teachers training was the subject of our study [19]. Regarding bilingual education, the analysis of literature sources showed that the theoretical foundations of bilingualism in Ukraine are reflected in the works of Baditsa, Kolesnyk and Polkhovska [3], Bodnarchuk [5], Goroshkina [6], Ihnatenko [7], Konoval et al [9], Kotlovskiy et al [10], Shirin [18], Sulik [20], Sytnyakivska and Khlyvnyuk [22], Ustymenko and Hamaniuk [23]. Their researches prove that bilingual education is a purposeful process of involvement in the world culture through native and foreign languages, when a foreign language acts as a means of cognizing the world, acquiring special knowledge, learning cultural, historical and social experience of different countries and peoples.…”
Section: Introductionmentioning
confidence: 99%
“…• Svitlana Amelina, National University of Life and Environmental Sciences of Ukraine, Ukraine [1] • Oksana Chernysh, Zhytomyr Polytechnic State University, Ukraine [36] • Vita Hamaniuk, Kryvyi Rih State Pedagogical University, Ukraine [35] • Věra Höppnerová, Westböhmische Universität Pilsen, Czech Republic [7] • Valentyna Karpiuk, Kryvyi Rih State Pedagogical University, Ukraine [9] • Yuliya Kazhan, Mariupol State University, Ukraine [10] • Svetlana Kovpik, Kryvyi Rih State Pedagogical University, Ukraine [21] • Vahid Norouzi Larsari, Charles University, Czech Republic [28] • Alla Lobanova, Kryvyi Rih State Pedagogical University, Ukraine [15] • Lyudmyla Lutsenko, Kryvyi Rih State Pedagogical University, Ukraine [17] • Rusudan Makhachashvili, Borys Grinchenko University, Ukraine [29] • Iryna Mintii, Kryvyi Rih State Pedagogical University, Ukraine [22] • Ümit Özkanal, Eskişehir Osmangazi Üniversitesi [24] • Halyna Pavlyshyn, University of Tasmania, Australia [3] • Iryna Piankovska, Volodymyr Vynnychenko Central Ukrainian State University, Ukraine [27] • Thorsten Roelcke, Technische Universität Berlin, Germany [26] • Doris Sava, Universitatea "Lucian Blaga" din Sibiu, Romania [18] • Serhiy Semerikov, Kryvyi Rih State Pedagogical University, Ukraine [32] • Mateusz Świetlicki, University of Wrocław, Poland [31] • Yana Topolnyk, Donbas State Pedagogical University, Ukraine [6] • Maryna Vardanian, Heidelberg University, Germany [38] • Søren Wichmann, University of Kiel, Germany [40]…”
Section: Program Committeementioning
confidence: 99%